The role of the Teach-Qual Model on Students’ mathematics interests: The mediating effects of students’ perception on mathematics - Asare, Bright; Yaribatuah, Peter; Ohene Boateng, Francis; Appiagyei, Ebenezer (Nashir Al-Kutub Indonesia, 2023)
This work aimed to examine the role of Teach-Qual (Teachers Quality) model on student’s mathematics interest as mediated by student’s perception in mathematics. The study sample 300 students from three senior high schools found in the Ashanti Region of Ghana using Convenience, stratified sampling, and simple random sampling. The study is purely a quantitative method which employed questionnaire as a data collection tool. The data was analyzed by using Amos (Ver. 23) for estimating the result for the hypothesis path. The outcome of this study revealed that, teacher-student’s-collaboration and teacher empathy yielded a direct positive and statistically improved impact on student’s maths interest. Student’s perception in mathematics partially mediates the association between teacher empathy as well as student’s mathematics interest. Moreover, perception in mathematics partially mediates the relationship between teacher-student’s-collaboration and student’s maths interest. The study recommended mathematics teachers to collaborate with students in terms of classroom teaching and learning, work more practical mathematics examples with students in the class in order to enhance student’s mathematics interest.